Effect of charge loading during electrocoagulation in dairy wastewater - Cachay Melly, Jaime Alberto (2022)
Electrocoagulation is frequently studied considering only the current or current density as a determining parameter when looking for the optimal conditions of wastewater treatment; however, these are correlated to the charge loading parameter that regulates the dose of metal to be dissolved. Due to this, the present study incorporates the charge loading to find the optimal conditions of treatment by electrocoagulation to the effluents of a dairy industry, “La Planta Piloto de Leche” of Universidad Nacional Agraria La Molina, taking as a variable response to the removal of turbidity. Work has been done in batch on prototypes of 2.2 liters of effective capacity. The aluminum and iron electrodes, acting as anode and cathode respectively, were the best materials for the treatment, in addition, the highest turbidity removal was achieved at a pH of 8 and a charge flow of 5.65 F/m3, achieved at 2 Ampere (2A) of supplied current and 10 minutes of treatment. Subsequently, the test under a constant load flow (5.65 F/m3) reaffirmed that at 2A and 10 minutes of electrochemical treatment, the highest removals of contaminants, mainly oils and greases, and turbidity are achieved.